TRAINING ON MAKING CLEAN WATER PROCESSING UNITS FOR PERMANENT RESIDENTIAL COMMUNITIES I NANGBELAWAN VILLAGE I SIMPANG EMPAT DISTRICT KARO REGENCY: PELATIHAN PEMBUATAN UNIT PENGOLAH AIR BERSIH MASYARAKAT HUNIAN TETAP I DESA NANGBELAWAN I KECAMATAN SIMPANG EMPAT KABUPATEN KARO - Haesti Sembiring; Riyanto Suprawadi; Nelson Tanjung (Yayasan Education and Social Center, 2022)
The eruption of Mount Sinabung in Karo Regency from 2010 to 2018, forced residents around the slopes of the mountain to evacuate to a safe place. There are 5 sub-districts affected, namely Simpat Empat, Naman Teran, Payung, Munthe and Tiganderket sub-districts. This mountain has never erupted since 1600. As a result of this eruption the government has designated 3 Temporary Residential Locations (Huntara) and 33 locations designated as Permanent Residential (Huntap). Huntap I Nangbelawan Village I is one of 33 independent relocation sites known as Permanent Residential (Huntap) which has been provided by the Karo Regency government until 2019. The Karo Regency Government has carried out a lot of development in Huntap refugee camps such as entrance facilities, electricity , drainage, communal, worship facilities, health facilities and clean water. The clean water facility built by the government is in the form of drilled wells. Based on oblivion observations, the levels of lead (Pb) in community bore well water caused the existence of air shelters for several residents visited by the team. Based on these problems, training activities for making clean water treatment units were carried out in permanent residential communities I Nangbelawan I Village, Simpang Empat District, Karo Regency. Solving the problem of water quality from drilled wells for the shelter I community, Nang Belawan Village, Simpang Empat District, Karo Regency by the community service team from Poltekkes, Ministry of Health, Medan, Department of Environmental Health, was carried out by suggesting that a building/water treatment unit be constructed using a combination method of sand filter and up-flow activated carbon.